A study to compare two goniometric methods for measuring active pronation and supination range of motion. (June 2013) - Cimatti, Bruno; Marcolino, Alexandre M; Barbosa, Rafael I; De Cássia Registro Fonseca, Marisa
Introduction: Movement of the forearm allows positioning the hand during several functional activities of daily living. Assessing range of motion of supination and pronation is essential for clinical identification of functional limitations, although many methods can be used. Confounding values can be found due to different techniques used by therapists. The purpose of this study was to compare two standard goniometric methods for measuring active range of motion of forearm pronation and supination, aiming to define its reliability and ease of use. Methods: The study included 33 individuals, 13 injured and 20 non-injured volunteers. We analyzed two standard goniometric methods for measuring pronation and supination. For the first method, the volunteers had to hold a pencil as a guide for the movable arm of the goniometer and for the second method the movable arm was in contact with the distal dorsal surface of the wrist near the ulna head, and the hand was free. Two trained examiners performed the evaluations. Intraclass correlation coefficient and limits of agreement of Bland and Altman were used to analyze the data. Results: Intraclass correlation coefficient values were excellent for both groups and movements at inter-rater and inter-methods comparison. Bland and Altman plots showed that, although excellent reliability, some data dispersion was present. Conclusion: These data suggest that both methods could be used in clinical practice with excellent reliability. The goniometric method with the movable arm placed in contact with the distal dorsal surface of the wrist near the ulna head might be easier to perform and useful in cases where finger prehension is absent or weak, which would prevent the use of a pencil as reference.